Concept COMMUNITY in Autobiography by Barack Obama “Dreams from my Father” - O. B. Nesterova (Научный диалог)
The article is devoted to the concept of COMMUNITY as one of the components of the concept sphere of language personality of Barack Obama in his early political career. The material for the study is his first autobiographical work - “Dreams from my Father”. The methods of conceptual, semantic and discourse analysis are used. An attempt was made to reconstruct the concept of COMMUNITY by studying the characteristics of its linguistic expression. Objectives of the study include a description of the means of objectification of this concept in this work and the construction of the nominative field with highlighting of conceptual signs. Regular actualization of the concept in this work allows to conclude that COMMUNITY is one of the central concepts that form the concept sphere of Barack Obama at the time of writing “Dreams from my Father.” In addition to the function of reflection of the author’s inner world and his personal values, the appeal to this concept has the function of the impact on the reader and it generates and reinforces in the minds of readers (and hence public) designing politician’s image. The concept of COMMUNITY by Barack Obama has a complicated structure and includes a number of other complex concepts, having axiological load and important to the majority of American citizens, such as IDENTITY, RESPONSIBILITY, COMMITMENT, UNITY and some others.